Leben erzählen - Leben verstehen Dimensionen der Biografieforschung und Narrativer Interviews für die Erwachsenenbildung - Horsdal, Marianne (Theorie und Praxis der Erwachsenenbildung, 2013)
"Over the past few years, narrative research as central method for empirical social research has broadened the view of interdisciplinary approaches. This also benefits the adult education research, as for example within the areas of literacy and basic education.The exploration of (auto)biographical narrative styles and structures contributes greatly to the understanding of learning biographies. In this book the author combines several international studies and links them to issues from within adult education research. The studies thereby capture neurobiological, philosophical and pedagogical perspectives of narrative structures. They reveal links between biographies and educational processes and allow for the initiation of new teaching/learning settings."